2015
DOI: 10.1128/jvi.00986-15
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Relationship between Human Cytomegalovirus pUL27 and pUL97 Activities during Infection

Abstract: Human cytomegalovirus (HCMV) is a member of the betaherpesvirus family. During infection, an array of viral proteins manipulates the host cell cycle. We have previously shown that expression of HCMV pUL27 results in increased levels of the cyclindependent kinase (CDK) inhibitor p21Cip1 . In addition, pUL27 is necessary for the full antiviral activity of the pUL97 kinase inhibitor maribavir (MBV). The purpose of this study was to define the relationship between pUL27 and pUL97 and its role in MBV antiviral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…R25 blocks activity of CDK1, CDK2 and CDK5) (Sandal et al, 2002;Soni & Jacobberger, 2004). Consistent with our data, R25 treatment has been shown to reduce viral titres by approximately 1.2 log units, even at a much lower dose of 150 nM (Bigley et al, 2015). The identification of the CDK1-pUL50 interaction by CoIP analysis in the present study further suggests that at least CDK1 is directly involved in core NEC formation.…”
Section: Discussionsupporting
confidence: 91%
“…R25 blocks activity of CDK1, CDK2 and CDK5) (Sandal et al, 2002;Soni & Jacobberger, 2004). Consistent with our data, R25 treatment has been shown to reduce viral titres by approximately 1.2 log units, even at a much lower dose of 150 nM (Bigley et al, 2015). The identification of the CDK1-pUL50 interaction by CoIP analysis in the present study further suggests that at least CDK1 is directly involved in core NEC formation.…”
Section: Discussionsupporting
confidence: 91%
“…Studies by Hamirally and Kamil et al [52] have demonstrated that phosphorylation of LMNA contributes to nuclear egress of HCMV particles. The antiviral compound, maribavir inhibits this process and its antiviral activity is further supported by increased steady-state levels of CDKN1A (p21 CIP1 ) ( Fig 6C) [51,54,70]. It is important to note that the kinetics of mitotic entry are regulated by the HCMV protein pUL21a which suppresses Cyclin A levels ( Fig 9A) [55].…”
Section: Plos Computational Biologymentioning
confidence: 95%
“…This state includes disruption of the nuclear lamina by and k 0 f 11 are high, respectively. https://doi.org/10.1371/journal.pcbi.1007733.g008 phosphorylation of LMNA by both HCMV pUL97 kinase and MPF kinase (CCNB1:CDK1) which is required for virion particle nuclear egress [51][52][53][54]. Disrupting these kinases is the defined mechanism of action for the antiviral, Maribavir [52,54].…”
Section: Defining the Contribution Of Apc/c Degradation To Mitotic Comentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in UL27-positive cells, p21 levels are high, cellular Cdks are inhibited, and Rb is phosphorylated during infection only if UL97 is present and active. In UL27-negative cells, p21 levels are low (54), and as a result, cellular Cdks are active and able to phosphorylate Rb. Rb phosphorylation by cellular Cdks or UL97 can be easily distinguished by monitoring the residues serine 249 and threonine 252, which are phosphorylated by cellular Cdks but not UL97 (2).…”
Section: Deoxyribonucleotides Are Limiting For Hcmv Dna Replicationmentioning
confidence: 99%